Bhartr̥hari, language, thought and reality : proceedings of the international seminar, Delhi, December 12-14, 2003 - International Seminar on Bhartr̥hari: Language, Thought, and Reality (2003 : New Delhi, India); Caturvedī, Mithileśa (Delhi : Motilal Banarsidass Publishers, 2009)
Contributed research papers presented at three day International Seminar on Bhartr̥hari: Language, Thought, and Reality at the India International Centre, New Delhi on Dec. 12-14, 2003 organised as part of the centenary celebration of Motilal Banarsidass.
Sadrži bibliografske bilješke.
"A bibliography on Bhartrhari [by] Yves Ramseier": str. [557]-612.
Sadrži odjeljke na sanskrtu.
Keywords: sanskrt -- sanskrtska gramatika; Bhartr̥hari -- Vākyapadīya; indijska filozofija jezika -- semantika - filozofija; Bhartr̥hari i Patanjali -- teorija jezika; Bhartr̥hari i Humboldt -- kognitivna lingvistika